Disruption of childhood vaccination during the COVID-19 pandemic in Indonesia - Fahriani, Marhami; Anwar, Samsul; Yufika, Amanda; Bakhtiar, Bakhtiar; Wardani, Elly; Winardi, Wira; Akel, Kaitlyn B.; Wagner, Abram L.; Harapan, Harapan (Narra J, 2021)
The aim of this study was to assess the magnitude of childhood vaccination disruption and to determine the predictors of delaying childhood vaccinations during the coronavirus disease 2019 (COVID-19) pandemic among Indonesian parents. We conducted a nationwide, online, cross-sectional study. A set of questionnaires assessed the disruption of childhood vaccinations and possible explanatory variables, including demographic characteristics, current underlying disease, exposure to and confidence in COVID-19 information, perceived risk, attitude and practice on vaccination, and COVID-19 prevention practice. A multivariable linear regression was used to characterize the relationship between explanatory variables and delayed childhood vaccination. We included 1137 respondents for analysis, of which 52.6% were males and 58.4% participants aged between 31 and 50-years old. Disruption of childhood vaccination service in local health facilities was reported in 42.2% (480/1137) of respondents and 13.3% (193/1137) of respondents explained that their children could not be vaccinated because a healthcare facility temporary stopped the vaccination service. Of all respondents, 312 (27.4%) delayed vaccinating their children for a compulsory vaccination shot. Factors associated with higher odds of delaying compulsory vaccinations for children were employment and chronic disease status, flu vaccination status in the past year, and prior COVID-19 infection. In conclusion, there was a significant disruption of childhood vaccination practices in Indonesia during the COVID-19 pandemic. This is not only due to healthcare closures but also due to parents’ practice - delaying the compulsory childhood vaccination for their children. We urge the government to strengthen strategies to ensure childhood vaccination services are available to all children in the country during a pandemic.